2019
DOI: 10.3847/1538-4357/ab4c36
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Massive Black Holes at High-z via Accretion Predominantly Driven by Magnetic Outflows

Abstract: Luminous quasars powered by accreting supermassive black holes (SMBHs) have been found in the early Universe at z 7.5, which set a strong constraint on both the seed black hole mass and the rapid growth of the SMBHs. In this work, we explore how the SMBHs are grown through Eddington limited accretion driven predominantly by magnetic outflows. Most angular momentum and the released gravitational energy in the disk can be removed by magnetic outflows, and therefore the mass accretion rate of the black hole (BH) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…The main difficulty of this disk instability model for QPEs is the viscous timescale of the thin accretion disk being significantly larger than the observed periods of QPEs (e.g., Pan et al 2021Pan et al , 2022. It was suggested that the viscous timescale of a disk driven predominantly by magnetic outflows can be substantially shortened (Cao & Spruit 2013;Li & Begelman 2014;Li & Cao 2019;Feng & Cao 2021;Kaur et al 2023;Pan et al 2022;Śniegowska 2023). Pan et al (2022) constructed an instability model of the disk with magnetically driven outflows for the QPEs of GSN 069, and both its light curve and phased-resolved X-ray spectra have been fitted by their model fairly well.…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulty of this disk instability model for QPEs is the viscous timescale of the thin accretion disk being significantly larger than the observed periods of QPEs (e.g., Pan et al 2021Pan et al , 2022. It was suggested that the viscous timescale of a disk driven predominantly by magnetic outflows can be substantially shortened (Cao & Spruit 2013;Li & Begelman 2014;Li & Cao 2019;Feng & Cao 2021;Kaur et al 2023;Pan et al 2022;Śniegowska 2023). Pan et al (2022) constructed an instability model of the disk with magnetically driven outflows for the QPEs of GSN 069, and both its light curve and phased-resolved X-ray spectra have been fitted by their model fairly well.…”
Section: Introductionmentioning
confidence: 99%
“…The disk winds can be served as the mechanism for the variable column density and absorprtion lines (Proga & Kallman 2004;Sim et al 2010;Tombesi et al 2012;Gofford et al 2015;Miller et al 2016;Braito et al 2021), which can be driven by radiation pressure etc. (e.g., King & Pounds 2015;You et al 2016;Li & Cao 2019). The anticorrelation of N H − L 2−10keV /L Edd or N H − Γ suggest that the absorption material most possibly correlated with the accretion process (see left and right panels in Fig.…”
Section: Evolution Of Nmentioning
confidence: 97%
“…In this case, the distribution of BH spins is mainly determined by ∆M/M, the fractional BH mass increase in each episode. If ∆M/M 1, The disk angular momentum in each episode is large enough to drive the BH to high spin no matter what the initial spin is; while in episodes with ∆M/M 1 BH tends to spin down, because the BH mass increases linearly with the number of accretion episodes N acc while the angular momentum gain is proportional √ N acc due to the random-walk cancellation (King & Pringle 2006;King et al 2008;Wang et al 2009;Dotti et al 2013;Volonteri et al 2013;Li & Cao 2019;Zhang & Lu 2019).…”
Section: Accretionmentioning
confidence: 99%